Types and Roles of Topic Shift Markers in Non Face-to-Face Conversation in Thai - Sabua, Yanisa; Panpothong, Natthaporn (Journal of Arts and Thai Studies, 2024)
Objectives: This article aims to study types and roles of topic shift markers in non face-to-face conversation in Thai. Methods: The data were collected from 30 telephone conversations and 200 LINE and Facebook Messenger conversations. It contains 230 conversations in total. Results: The results reveal that there are 10 types of topic shift markers including 1) Cohesive markers, 2) Markers expressing sudden thought, 3) Markers of calling the other party, 4) Markers expressing emotions, 5) Markers of getting interlocutor’s attention, 6) Markers indicating topic, 7) Conclusion markers, 8) Markers of ending topic, 9) Markers indicating interrogation, and 10) Markers of invitation. These markers serve 8 roles, in topic shifting, that is 1) To indicate topic shift, 2) To link a new topic with the preceding or prior topic, 3) To express a sudden thought, 4) To attract the other party’s attention, 5) To express the speaker’s emotions, 6) To indicate main ideas of the new topic, 7) To make a conclusion from common knowledge, and 8) To indicate the speaker’s intention. Every type of markers plays a role of indicating topic shift. In addition, each type also has a particular function. Application of this study: The study yields insight into topic shift in Thai non face-to-face conversation. It can also be used as a model to study topic shift in other types of conversation.